Komposisi Tubuh pada Atlet Finswimming : Analisis Korelasi - Ammar Santoso, Gafur (STKIP Muhammadiyah Kuningan, 2024)
This study aims to analyze the body composition of athletes from the West Java finswimming team and to explore the correlations between various body composition metrics. The sample comprises 8 athletes whose body composition was assessed using Tanita Body Composition DC-360S. Key metrics evaluated include weight, fat mass (FATMASS), fat-free mass (FFM), muscle mass (MUSCLEMASS), total body water (TBW), and bone mass (BONEMASS). Correlation analysis demonstrates significant positive relationships between weight and other body composition metrics, particularly fat-free mass (Pearson correlation = 0.966, p < 0.001), muscle mass (Pearson correlation = 0.964, p < 0.001), total body water (Pearson correlation = 0.973, p < 0.001), and bone mass (Pearson correlation = 0.994, p < 0.001). These findings underscore the interconnected nature of body composition variables and their potential impact on athletic performance. The study provides valuable insights into the body composition profiles of finswimmers, which can inform tailored training and nutritional strategies to enhance athletic performance. Future research should focus on longitudinal studies to assess the effects of specific interventions on these metrics over time.